1995
DOI: 10.1149/1.2044315
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Arsenic Autodoping with Rapid Thermal Epitaxy for Low Power Bipolar Complementary Metal Oxide Semiconductor

Abstract: Scaled bipolar transistors for bipolar complementary metal oxide semiconductor (BiCMOS) integrated circuits require low collector-substrate capacitance in order to minimize power consumption. The unintentional incorporation of dopant into a growing epitaxial layer, known as autodoping, can affect the ultimate lower limit of the collector-substrate capacitance. In this work, we studied the effects of epitaxial layer growth rate, arsenic-buried layer implant dose, and pre-epitaxia] bake temperature on autodoping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The formation of these Eu-O complexes appears to be more beneficial to the crystal quality and stability than either defect is on its own [232]. Actually, during the growth of nitrides and oxides, unintentional As and B impurities were also observed [233][234][235].…”
Section: Other Impuritiesmentioning
confidence: 99%
“…The formation of these Eu-O complexes appears to be more beneficial to the crystal quality and stability than either defect is on its own [232]. Actually, during the growth of nitrides and oxides, unintentional As and B impurities were also observed [233][234][235].…”
Section: Other Impuritiesmentioning
confidence: 99%
“…Agnello et al 5 have shown that when low temperature AP-CVD is used with DCS as the Si source, it is possible to incorporate a very high As concentration of 2 ϫ 10 21 cm Ϫ3 . Moreover, the growth rate is enhanced in a manner similar to that of P. J. H. Comfort et al 3 have also grown epi layers with a high As concentration (7 ϫ 10 19 cm Ϫ3 ) by using silane based plasma-enhanced CVD. With this technology, a higher growth rate can be achieved than with DCS, but generally, it has a higher defect density.…”
mentioning
confidence: 89%
“…This undesirable effect is generally referred to as autodoping. [1][2][3] With low temperature, atmospheric pressure CVD (AP-CVD) using SiCl 2 H 2 (DCS) as the Si source, Sedgwick et al 4 have shown that highly phosphorus-doped Si layers with a low defect density can be grown. By growing very sharp P profiles, they demonstrated that the P concentration in the epi layer can be controlled directly by adjusting the phosphine concentration in the H 2 carrier gas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 The effect of the surface segregation is to hamper any abrupt transition to another doping level, and, in the case of an abrupt drop in doping, the undesired lingering of the higher As doping is referred to as autodoping. Previous experimental investigations have focused on exploring the optimal conditions for achieving goals such as suppressing lateral autodoping, 6 determining the impact on the growth rate, 7 growing highly-doped layers of poly-Si, 8 or Ge x Si 1Àx alloys. 9 By the analysis of the mechanism governing the doping from the As segregated layer, good results were in the past achieved and applied to the growth of high-doped abrupt As peaks.…”
Section: Introductionmentioning
confidence: 99%